Beta Rebound as an Index of Temporal Integration of Somatosensory and Motor Signals - Cardellicchio, Pasquale; Hilt, Pauline M.; Dolfini, Elisa; Fadiga, Luciano; D’Ausilio, Alessandro (Frontiers in Systems Neuroscience, 2020)
Modulation of cortical beta rhythm (15-30 Hz) is present during preparation and execution of voluntary movements as well as during somatosensory stimulation. A rebound in beta synchronization is observed after the end of voluntary movements as well as after somatosensory stimulation and is believed to describe the return to baseline of sensorimotor networks. However, the contribution of efferent and afferent signals to the beta rebound remains poorly understood. Here we applied an electrical median nerve stimulation (MNS) to the right side followed by Transcranial Magnetic Stimulation (TMS) on the left primary motor cortex after either 15 or 25 ms. Since the afferent volley reaches the somatosensory cortex after about 20 ms, TMS on the motor cortex was either anticipating or following the cortical arrival of the peripheral stimulus. We show modulations in different beta sub-bands and in both hemispheres, following a pattern of greater resynchronization when motor signals are paired with a peripheral one. The beta rebound, in the left hemisphere (stimulated), is modulated in its lower frequency range when TMS precede the cortical arrival of the afferent volley. In the right hemisphere (un-stimulated) instead, the increase is limited to higher beta frequencies when TMS is delivered after the arrival of the afferent signal. In general, we demonstrate that the temporal integration of afferent and efferent signals plays a key role in the genesis of the beta rebound and that these signals may be carried in parallel by different beta sub-bands.